2012
DOI: 10.4103/0970-0358.96595
|View full text |Cite
|
Sign up to set email alerts
|

Firecracker injuries during Diwali festival: The epidemiology and impact of legislation in Delhi

Abstract: Setting and Design:A hospital-based retrospective study of firecracker-related injuries was carried out at a government sponsored hospital in Delhi.Materials and Methods:1373 patients attended the emergency burn care out-patients clinic during 2002–2010 pre-Diwali, Diwali and post-Diwali days. Every year, a disaster management protocol is revoked during these 3 days under the direct supervision of the Ministry of Health and Family Welfare, Government of India.Results:There was an increase in the number of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…There is an obvious male preponderance, and the usual victims are between 5 and 30 years with the Anar (flower pot) being the most common causative agent, closely followed by Bombs (sound-emitting fireworks). [ 1 2 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an obvious male preponderance, and the usual victims are between 5 and 30 years with the Anar (flower pot) being the most common causative agent, closely followed by Bombs (sound-emitting fireworks). [ 1 2 ]…”
mentioning
confidence: 99%
“…There are conflicting reports regarding the incidence of firecracker related injuries as Tandon et al [ 1 ] found that the incidence is steadily increasing while Puri et al have suggested that the incidence is decreasing. [ 2 ] Injuries specific to the preauricular region don’t usually present as a temporal artery rupture but rather the presentation is that of a temporal artery pseudoaneurysm, also called ‘puck aneurysms’[ 3 ] or ‘squash ball aneurysms’.…”
mentioning
confidence: 99%
“…Conduction of awareness campaigns, improvement in education facilities and provision of protective bodywear to the workers should also be practiced regularly for maintaining safety of employees in such factories. 2,10 Besides similar asteroid corneas require a proper documentation as they may be mistaken for additional serious ocular conditions by other ophthalmologists in the future if the affected individual fails to recall their characteristic history in lieu of its benign nature. To conclude, ocular trauma from fireworks commonly affects young males and often results in serious and visionthreatening yet preventable complications.…”
Section: Discussionmentioning
confidence: 99%
“…[2122232425] Even in Delhi, the National Capital of India which already has very high levels of air pollution at baseline, burning of firecrackers during Diwali has been shown to increase the levels of PM pollution even further. [26] Apart from burn injuries[27] and noise pollution,[28] air pollution due to the burning of firecrackers has been shown to cause respiratory tract infections, worsening of asthma, COPD, cardiovascular diseases, and even premature deaths. [2930313233] Taking cognizance of the concerns of the ambient air pollution catastrophe during the Diwali festival, the Supreme Court of India banned the sales of firecrackers in 2017.…”
Section: Discussionmentioning
confidence: 99%